A robust response to combination immune checkpoint inhibitor therapy in HPV-related small cell cancer: a case report. Issue 1 (9th May 2018) - Ho, Won Jin; Rooper, Lisa; Sagorsky, Sarah; Kang, Hyunseok
Abstract : Background: Human papillomavirus-related small cell carcinoma of the head and neck is an extremely rare, aggressive subtype with poor outcomes. Therapeutic options are limited and are largely adopted from small cell lung cancer treatment paradigms. Case presentation: This report describes a 69-year old male who was diagnosed of HPV-related oropharyngeal cancer with mixed small cell and squamous cell pathology which was clinically aggressive and progressed through multimodal platinum-based therapies. Upon manifestation of worsening metastatic disease, the patient was initiated on a combination of ipilimumab and nivolumab. Within 2 months of starting immunotherapy, a robust partial response was observed. During the treatment course, the patient developed immune-related adverse effects including new diabetes mellitus, colitis, and hypothyroidism. The disease-specific survival was 26 months. Conclusion: Combination immunotherapy may be an attractive option for HPV-related small cell head and neck cancers resistant to other treatment modalities and thus warrants further evaluation.